2009
DOI: 10.1002/hep.22679
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of relapse after a short (12 weeks) course of antiviral therapy and re-treatment efficacy of a prolonged course in patients with chronic hepatitis C virus genotype 2 or 3 infection #

Abstract: In hepatitis C virus (HCV) genotypes 2 and 3 patients, the high rate of relapse after 12 to 16 weeks of antiviral therapy is the main concern for shortening treatment duration. This study was undertaken to delineate predictors of relapse after short treatment in patients with undetectable HCV RNA at treatment week 4 (RVR), and to report in RVR patients with relapse the sustained virological response (SVR) after a second 24-week course of therapy. RVR patients received pegylated interferon (Peg-IFN) alfa-2b (1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 58 publications
1
64
1
1
Order By: Relevance
“…Previous reports indicated that viral factors (e.g., viral load, aa substitutions in the NS5A region, early viral kinetics, and periods from the start of treatment to initial point of undetectable HCV-RNA) and host factors (e.g., body mass index, fibrosis stage, and level of soluble interleukin-2 receptor) might be important predictors of treatment response to 24-week IFN + ribavirin combination therapy in patients infected with HCV genotype 2a, in addition to treatment-related factors (e.g., treatment duration and ribavirin dose) [6][7][8][9][23][24][25][26][27][28] . Using multivariate analysis, the present study identified viral-(viral load and substitution of aa 4) and host-related factors (age and serum albumin levels as surrogate markers of liver fibrosis [3,11] ) that influenced the virological response to 24-week combination therapy in patients with genotype 2a infection and a high viral load.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports indicated that viral factors (e.g., viral load, aa substitutions in the NS5A region, early viral kinetics, and periods from the start of treatment to initial point of undetectable HCV-RNA) and host factors (e.g., body mass index, fibrosis stage, and level of soluble interleukin-2 receptor) might be important predictors of treatment response to 24-week IFN + ribavirin combination therapy in patients infected with HCV genotype 2a, in addition to treatment-related factors (e.g., treatment duration and ribavirin dose) [6][7][8][9][23][24][25][26][27][28] . Using multivariate analysis, the present study identified viral-(viral load and substitution of aa 4) and host-related factors (age and serum albumin levels as surrogate markers of liver fibrosis [3,11] ) that influenced the virological response to 24-week combination therapy in patients with genotype 2a infection and a high viral load.…”
Section: Discussionmentioning
confidence: 99%
“…IFN + ribavirin combination therapy carries potential serious side effects and is costly, especially when used long enough to achieve a high SVR. For these reasons, especially in genotype 2 infection, it is necessary to identify those patients who could achieve SVR with a shorter treatment course ( ^ 16 weeks) to free them of unnecessary side effects and reduce costs, preferably as early as possible [6][7][8] . Identification of these viral and host factors before the start of combination therapy should help design better therapeutic regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…body mass index, fibrosis stage, and hepatocyte steatosis) might be important predictors of treatment response to IFN-related therapy in patients infected with HCV genotype 2a, in addition to treatment-related factors (e.g. treatment duration, and ribavirin dose) [6][7][8][9][10][11][21][22][23][24][25][26][27] . One of the lim- itations to this study is that due to the small number of patients we were not able to investigate treatment-resistant factors.…”
Section: Discussionmentioning
confidence: 99%
“…Intervirology 2010;53: [188][189][190][191][192] 189 especially in genotype 2 infection, it is necessary to identify those patients who could achieve SVR with a shorter treatment course (16 weeks or less) to free them of unnecessary side effects and reduce costs, preferably as early as possible [6][7][8] . However, we also sometimes encounter treatment-resistant patients infected with genotype 2 [3,10,11] .…”
Section: Hcv-2 and Extending Combination Therapymentioning
confidence: 99%